Treatment with etamsylate reduces haemolactia in lactating dairy cows. Issue 2 (30th April 2019) - Fraile, Lorenzo; Arcas, Antonio; Jiménez, Luis M.; Mallo, Josep; Armengol, Ramon
Abstract: This Research Communication describes the efficacy of etamsylate to reduce haemolactia in dairy cows. A dairy cow with haemolactia produces milk that is reddish or pinkish due to the presence of blood. Haemolactia causes economic loss because bloody milk is rejected by the industry and the consumers. A total of 58 dairy cows with haemolactia were included in the study and randomly divided into treated ( n = 31) and control ( n = 27) groups. Treatment consisted of three consecutive daily doses of etamsylate at 15 mg/kg, delivered intramuscularly. Milk production was recorded daily for 7 d, whether or not blood was detected in milk. The mean number of days with the presence of blood in milk in the treatment group was significantly lower (3·4 d) than in the control group (4·9 d). Treatment with etamsylate did not significantly affect milk yield. In conclusion, treatment with etamsylate reduces the number of days blood is observed in milk and it does not have any negative effect on milk production.